Perbedaan Kepuasan Pasien Peserta Askes Di Puskesmas & Praktek Dokter Keluarga Sebuah Balai Pengobatan Swasta Di Bandar Lampung - - Sulyaprilawati; Reni Zuraida (JUKE Unila, 2012)
Patient's satisfaction or consumer's satisfaction is one of the few indicators to measure the quality of health's services by using satisfaction measurement's survey. The aim of this research are to know the difference health satisfaction's level and the difference of health service's satisfaction of insurance participant patients (askes) at The Executive Health Service 1st Stage Puskesmas and family's doctor practice Clinical Centre in Bandar Lampung. This research is using escriptive-comparative method with cross sectional approach and accidental sampling. The sample consisted of 100 health insurance patients at public health centre and 99 patients at family's doctor practice. The analysis of this research is looking for the difference of mean's value statistically. To find out the difference meaning of value mean, this research is using Mann-Whitney U test as hypothesis's test. The result of the research showed that the difference health satisfaction's  level of insurance patients between The Executive Health Service 1st Stage public health centre and family's doctor practice is in the range enough until good (mean for the answer = 3,35 dan 3,46), there are differences satisfaction to the doctor's service factor and to the access of health's service factor (p = 0,002 dan p = 0,000), then there are no differences satisfaction to the physical movement factor and administration's service factor (p = 0,126 dan p = 0,112)